Mortality of Spanish soccer referees and coaches: a retrospective cohort study - Diz, J. C.; Rodriguez, I.; Iglesias-Sueiro, S.; Ferreira, E. D.; Sanchez-Lastra, M. A.; Ayán, C. (Science and Medicine in Football, 2024)
There is evidence that elite soccer players live longer than general population, but there is no information on soccer coaches and referees. We aimed to analyze the longevity of both professionals, comparing them with soccer players and with general population. In this retrospective cohort study, a total of 328 male Spanish soccer coaches, 287 referees, and 1230 soccer players, all born before 1950, were divided in two cohorts, matched 2:1 with coaches and referees. We compared the survival of the cohorts with the Kaplan-Meier estimator and significance with the log-rank test. We calculated hazard ratios of death for coaches and referees compared with male Spanish general population of the same period. Differences in survival among cohorts were found, but they did not reach statistical significance. The estimated median survival time was 80.1 years (95% CI 77.7-82.4) for referees, 78 years (95% CI 76.6-79.3) for coaches, 78.8 years (95% CI 77.6-80) for referees matched with players, and 76.6 years (95% CI 75.3-77.9) for coaches matched with players. Both coaches and referees had lower mortality than general population, but this advantage disappeared after 80 years of age. We found no differences in longevity among Spanish elite soccer referees, coaches and players born before 1950. Both coaches and referees had lower mortality than general population, but this advantage disappeared after 80 years of age.